Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.13057/biodiv/d210913
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of zooplankton community in Toli shad (Tenualosa toli) habitats, Sarawak, Malaysia

Abstract: Abstract. Aiman WM, Yusoff FM, Arshad A, Kamal AHM, Ismail J, Idris MH, Karim NU, Asif AA. 2020. Distribution of zooplankton community in Toli shad (Tenualosa toli) habitats, Sarawak, Malaysia. Biodiversitas 21: 4022-4033. The river ecosystems of Sarawak has been identified as important-spawning ground for economically important Toli shad (Tenualosa toli) fisheries. In these river ecosystems, zooplankton serves as a secondary producer to the different types of fish larvae including Toli shad. The productivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The richness of nutrients, accessibility of rich phytoplankton, and ocean circulation may have contributed to the diverse species and groups of zooplankton that were discovered. The results, however, are consistent with the research from Aiman et al (2020), Azmi et al (2016), Deepika et al (2019), Melo et al (2010), Matias-Peralta and Yusoff (2015). Abdul et al (2016) conducted a study in an estuary and found a relative abundance that was higher than any zooplankton species.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The richness of nutrients, accessibility of rich phytoplankton, and ocean circulation may have contributed to the diverse species and groups of zooplankton that were discovered. The results, however, are consistent with the research from Aiman et al (2020), Azmi et al (2016), Deepika et al (2019), Melo et al (2010), Matias-Peralta and Yusoff (2015). Abdul et al (2016) conducted a study in an estuary and found a relative abundance that was higher than any zooplankton species.…”
Section: Discussionsupporting
confidence: 91%
“…When compared to other periods, the tidal period had very high species equitability (Evenness), which suggests that the diversity of the plankton was declining (Adesalu and Nwankwo, 2008). Studies by Abu-Hena et al (2016), Aiman et al (2020), Deepika et al (2019), Ismail and Zaidin (2015) were found to have similar findings to the present study. Additionally, Simpson's Dominance Index (D), a measure of diversity, takes both the total number of species present and the relative abundance of each species into account.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Compared to the current study, Melo et al (2010) discovered significantly lower zooplankton abundance (4,759 to 7,113 individuals/m 3 ) in the southwestern Atlantic, and Azmi et al (2016) found zooplankton abundance (3,030±855.6 individuals/m 3 ) at Merambong Shoal Seagrass Area, which is also lower than densities recorded in the present study. Zooplankton density measurements from certain river estuaries in the Sarawak Region of Malaysia ranged from 447 to 27,812 individuals/m 3 (Aiman et al, 2020). Overall, past findings supported the current results (Bhavan et al, 2015;Dhanasekaran et al, 2017;Manickam, 2015;Manickam et al, 2012;Manickam et al, 2014;Manickam et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…Estuaries have been recognized for a long time as crucial locations for fish because of the multiple functions they serve: as nurseries, migration corridors, feeding grounds, and shelter areas (Mc. Lusky and Elliot 2004;Rezai et al 2011;Tumiran et al 2011;Hossain et al 2012;Zaleha et al 2013;Rahim et al 2014;Saifullah et al 2014;Paturej et al 2017;Eugenia et al 2019;Aiman et al 2020). Furthermore, to ensure their safety and long-term maintenance, it's essential to have a firm grasp on the ecosystem process (i.e., the operation of these transitional environments) (Franco et al 2008).…”
Section: Introductionmentioning
confidence: 99%